2014
DOI: 10.3310/hsdr02370
|View full text |Cite
|
Sign up to set email alerts
|

Improving the effectiveness of multidisciplinary team meetings for patients with chronic diseases: a prospective observational study

Abstract: BackgroundMultidisciplinary team (MDT) meetings have been endorsed by the Department of Health as the core model for managing chronic diseases. However, the evidence for their effectiveness is mixed and the degree to which they have been absorbed into clinical practice varies widely across conditions and settings. We aimed to identify the key characteristics of chronic disease MDT meetings that are associated with decision implementation, a measure of effectiveness, and to derive a set of feasible modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 112 publications
(157 reference statements)
1
89
0
3
Order By: Relevance
“…Certain targets for improvement can be identified, especially regarding structure and patient-centredness, both of which have been recommended in the literature to strengthen IPT meetings (14,26,27). Similar to the findings of our study, Xyrichis identified group size and composition, as well as clear goals and objectives as important indicators of successful teamwork (14).…”
Section: Discussionmentioning
confidence: 99%
“…Certain targets for improvement can be identified, especially regarding structure and patient-centredness, both of which have been recommended in the literature to strengthen IPT meetings (14,26,27). Similar to the findings of our study, Xyrichis identified group size and composition, as well as clear goals and objectives as important indicators of successful teamwork (14).…”
Section: Discussionmentioning
confidence: 99%
“…Greater multidisciplinarity was not necessarily associated with more effective decision making and MDT decisions (as measured by decision implementation). Decisions were also less likely to be implemented for patients living in more deprived areas 18. There is little presented in the literature specifically about experiences of CNS in the MDT; however, the work of Taylor and Ramirez13 for the National Cancer Action Team provided very detailed responses from cancer nurses as a subgroup.…”
mentioning
confidence: 99%
“…Like many MDTMs for benign conditions, ours developed from the needs of the department and local population . Given the complexity of otologic surgery, a designated opportunity to discuss future operative cases was considered valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary team meetings (MDTMs) are well‐established as an important part of patient care in the context of cancer diagnoses. MDTMs are more recently being employed in some specialties to discuss complex noncancer diagnoses, for example, for heart failure and stroke, in addition to the regular oncological meetings . Multidisciplinary team (MDT) working and decision making confers several benefits to the patient; however, it requires a significant amount of preparation, coordination, and resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation